Metode Pelaksanaan Pekerjaan Struktur Kolom Pada Proyek Pembangunan Passengger Terminal Building Bandara Internasional Dhoho Kediri - Nasikhin, Mohammad Khoirun (Jurnal Vokasi Teknik Sipil, 2023)
Infrastructure development in a city not only aims to improve people's welfare, but also has the potential to be an alternative for national economic, environmental and social recovery. To improve community welfare through infrastructure development, one of which is the construction of the Dhoho Kediri International Airport in Kediri Regency. One of the multi-storey building developments at Dhoho Kediri International Airport is the passenger terminal building. The function of the passenger terminal building is to serve all passenger activities from departure to arrival at the airport. The passenger terminal building requires a sturdy structure, one of which is a column structure. The research method used is observation and observation methods in the field. From the results of field observations and observations during the implementation of column work, the column structure work is divided into several stages. Preparation stage, steel stage, formwork installation, column casting, formwork dismantling and column maintenance. Based on these results, it can be seen that in implementing the column structure there are six stages that must be carried out sequentially so as to produce a quality column.